Static bioassay with Liza parsia exposed to DDVP, an organophosphate - Mohapatra, B C; Noble, A (Indian Journal of Fisheries, 2011)
DDVP, a water-soluble organophosphateinsecticide, is widely used in the Kolleruregion of Andhra Pradesh for the control ofectoparasites, such as Lernea and Argulus,on fishes (Muthu el al. 1988). DDVP is usedas medicine in salmon farming against thesea lice. The use of this chemical in salmonfanning, however, appears to have deleteriouseffects on marine invertebrates (Egidiusand Moester 1987). Stephanie Pain (1989)linked the epidemic of eye disease in salmonof the wild to the use of this chemical infarms. Acute toxicity tests of DDVP were,therefore, conducted on Liza parsia. Amongmullets, Liza parsia, along with Mugil cephalus,has gained considerable importance infish culture because of its resistance toenvironmental changes and easy availability.It was, therefore, selected for this study.